Robust quantum spin Hall state and quantum anomalous Hall state in graphenelike BC3 with adatoms. (26th July 2018) - Zhao, Yinchang; Chen, Xi; Dai, Zhenhong; Zhang, Chao; Lian, Chao; Zeng, Shuming; Meng, Sheng; Ni, Jun
Abstract: Two-dimensional (2D) topological insulators (TIs) and Chern insulators (CIs) promise quantum spin Hall (QSH) and quantum anomalous Hall (QAH) states without dissipation. By combining first-principles calculations with Wannier functions-based tight-binding (TB) modeling, we demonstrate that the graphenelike BC3, which was fabricated early in experiment, can become 2D TIs and CIs through suitable decoration of adatoms. For the thallium (Tl) decorated BC3 systems, three low-energy structures with the same stoichiometry of BC3 Tl, whose stabilities are verified by the ab initio evolutionary algorithm, are found to be robust 2D TIs with the largest topologically nontrivial band gap of about 224 meV. For the transition metal atoms adsorbed BC3, three (2 × 2) BC3 systems with one adatom of technetium (Tc), rhenium (Re), or ruthenium (Ru) are found to be good CIs with the ferromagnetic moments of 1 to 2 μ B, nontrivial gaps of 38–50 meV, and nonzero Chern numbers of −1 to 1. These properties indicate that the systems of graphenelike BC3 with adatoms are good platforms for the study of QSH and QAH effects.